2002
DOI: 10.1016/s0141-1136(01)00108-8
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium detoxification processes in the digestive gland of cephalopods in relation to accumulated cadmium concentrations

Abstract: The high concentrations of cadmium recorded in the digestive gland of cephalopods from various temperate and subpolar waters suggest that these molluscs have developed efficient cadmium detoxification mechanisms. The subcellular distribution of cadmium in the digestive gland cells was investigated in seven cephalopod species from the Bay of Biscay (France) and the Faroe Islands. In most species, cadmium was mainly found in the cytosolic fraction of the digestive gland cells, reaching up to 86% of the total cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
115
0
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(133 citation statements)
references
References 37 publications
11
115
0
7
Order By: Relevance
“…In the octopod Octopus vulgaris however, calcium concentration increases during the oocyte development, suggesting that this essential element could be obtained from seawater intake (Villanueva and Bustamante 2006). It has been previously demonstrated that the eggshell displays a selective permeability to dissolved trace elements, independently of their essential or non-essential character (Bustamante et al 2002, Lacoue-Labarthe et al 2008, and that changes in seawater pCO 2 conditions could affect these properties (Lacoue-Labarthe et al 2009). In this study, it is worth noting that, whatever the treatment, 45 Ca was detected in embryos' cuttlebones revealing that 1) the eggshell is permeable to calcium and 2) the cuttlebone formation is dependent on calcium uptake from seawater.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the octopod Octopus vulgaris however, calcium concentration increases during the oocyte development, suggesting that this essential element could be obtained from seawater intake (Villanueva and Bustamante 2006). It has been previously demonstrated that the eggshell displays a selective permeability to dissolved trace elements, independently of their essential or non-essential character (Bustamante et al 2002, Lacoue-Labarthe et al 2008, and that changes in seawater pCO 2 conditions could affect these properties (Lacoue-Labarthe et al 2009). In this study, it is worth noting that, whatever the treatment, 45 Ca was detected in embryos' cuttlebones revealing that 1) the eggshell is permeable to calcium and 2) the cuttlebone formation is dependent on calcium uptake from seawater.…”
Section: Discussionmentioning
confidence: 98%
“…Exchange between seawater and PVF is limited and selective in terms of water and molecules (Gomi et al 1986;de Leersnyder and Lemaire 1972), including pollutants (Bustamante et al 2002, Lacoue-Labarthe et al 2009. Due to the egg case serving as a diffusion barrier for respiratory gases (CO 2 , O 2 ), embryos are exposed to low PVF pO 2 (pO 2 < 6 kPa, Cronin andSeymour 2000, Gutowska and and to high pCO 2 in turn (pCO 2 > 0.4 kPa i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are particularly surprising for the digestive gland as it (a) has no direct contact with ambient seawater and (b) plays a major role in the digestive processes, including nutrient absorption. However, this organ is also involved in detoxification processes of xenobiotics in cephalopods (Cheah et al 1995, Bustamante et al 2002. Therefore, elevated concentrations in the digestive gland could result more from transfers from other organs accumulating compounds to be detoxified than from actual bioconcentration in the digestive gland itself.…”
Section: Discussionmentioning
confidence: 99%
“…2004.11.099 in their tissues (e.g. Miramand and Bentley, 1992;Bustamante, 1998;Bustamante et al, 1998aBustamante et al, ,b, 2000Bustamante et al, , 2002aStorelli and Marcotrigiano, 1999). Among tissues, the digestive gland and branchial hearts appeared to play a major role in bioaccumulation processes of toxic elements such as cadmium and silver, which are detoxified and sequestrated, sometimes over a very long time scale (Bustamante et al, 2002a(Bustamante et al, , 2004Beuerlein et al, 2002).…”
Section: Introductionmentioning
confidence: 99%